Systemic Chemotherapy Is Modulated by Platelet-Activating Factor-Receptor Agonists - Ravi P. Sahu; Matheus Ferracini; Jeffrey B. Travers (Mediators of Inflammation)
Chemotherapy is used to treat numerous cancers including melanoma. However, its effectiveness in clinical settings is often hampered by various mechanisms. Previous studies have demonstrated that prooxidative stressor-mediated generation of oxidized lipids with platelet-activating factor-receptor (PAF-R) agonistic activity induces systemic immunosuppression that augments the growth of experimental melanoma tumors. We have recently shown that treatment of murine B16F10 melanoma cells in vitro or tumors implanted into syngeneic mice and treated intratumorally with various chemotherapeutic agents generated PAF-R agonists in a process blocked by antioxidants. Notably, these intratumoral chemotherapy-generated PAF-R agonists augmented the growth of secondary (untreated) tumors in a PAF-R dependent manner. As both localized and systemic chemotherapies are used based on tumor localization/stage and metastases, the current studies were sought to determine effects of PAF-R agonists on systemic chemotherapy against experimental melanoma. Here, we show that systemic chemotherapy with etoposide (ETOP) attenuates the growth of melanoma tumors when given subsequent to the tumor cell implantation. Importantly, this ETOP-mediated suppression of melanoma tumor growth was blocked by exogenous administration of a PAF-R agonist, CPAF. These findings indicate that PAF-R agonists not only negatively affect the ability of localized chemotherapy but also compromise the efficacy of systemic chemotherapy against murine melanoma.